Physiologic Frailty and Neurocognitive Decline Among Young-Adult Childhood Cancer Survivors: A Prospective Study From the St Jude Lifetime Cohort. Issue 31 (1st November 2021) - Williams, AnnaLynn M.; Krull, Kevin R.; Howell, Carrie R.; Banerjee, Pia; Brinkman, Tara M.; Kaste, Sue C.; Partin, Robyn E.; Srivastava, Deokumar; Yasui, Yutaka; Armstrong, Gregory T.; Robison, Leslie L.; Hudson, Melissa M.; et al.
Abstract : PURPOSE: Eight percent of young-adult childhood cancer survivors meet criteria for frailty, an aging phenotype associated with poor health. In the elderly general population, frailty is associated with neurocognitive decline; this association has not been examined in adult survivors of childhood cancer. METHODS: Childhood cancer survivors 18-45 years old (≥ 10 years from diagnosis) were clinically evaluated for prefrailty or frailty (respectively defined as ≥ 2 or ≥ 3 of: muscle wasting, muscle weakness, low energy expenditure, slow walking speed, and exhaustion [Fried criteria]) and completed neuropsychologic assessments at enrollment (January 2008-June 2013) and 5 years later. Weighted linear regression using inverse of sampling probability estimates as weights compared differences in neurocognitive decline in prefrail and frail survivors versus nonfrail survivors, adjusting for diagnosis age, sex, race, CNS–directed therapy (cranial radiation, intrathecal chemotherapy, and neurosurgery), and baseline neurocognitive performance. RESULTS: Survivors were on average 30 years old and 22 years from diagnosis; 18% were prefrail and 6% frail at enrollment. Frail survivors declined an average of 0.54 standard deviation (95% CI, −0.93 to −0.15) in short-term verbal recall, whereas nonfrail survivors did not decline (β = .22; difference of βs = −.76; 95% CI, −1.19 to −0.33). Frail survivors declined more than nonfrail survivors on visual-motor processing speed (β = −.40; 95% CI, −0.67 to −0.12), cognitive flexibility (β = −.62; 95% CI, −1.02 to −0.22), and verbal fluency (β = −.23; 95% CI, −0.41 to −0.05). Prefrail and frail survivors experienced greater declines in focused attention (prefrail β = −.35; 95% CI, −0.53 to −0.17; frail β = −.48; 95% CI, −0.83 to −0.12) compared with nonfrail survivors. CONCLUSION: Over approximately 5 years, prefrail and frail young-adult survivors had greater declines in cognitive domains associated with aging and dementia compared with nonfrail survivors. Interventions that have global impact, designed to target the mechanistic underpinnings of frailty, may also mitigate or prevent neurocognitive decline.